ANALISIS METODE BERCERITA PADA ANAK USIA 5-6 TAHUN - Panjaitan, Aryani Ayu Sariska; Radiana, Usman; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis is research purposes to analyze story method by teacher for children in age 5 to 6 yearsat Kindergarten of Saint Maria Pontianak. This method is useful is descriptive which containÂ  a qualitative research. The source of data is a teacher of kindergarten of grade B of Saint Maria. Her name is Inneke kesuma Arti, S. Pd. She is 49 years old. She is a woman, the result of research and documentation of her activities.the result of research shows the story application method for students in ages 5-6 years in Saint Maria school Pontianak. The conclusion is the story application strategy that done by teacher in the class enough good but must improves about variation from this application such as media and the prepare of the teacher to tell the story. Teacher also reaches the goals very good and also able to implementate the story method with step by step. Moral themselves Â Keywords: Analyze, Story Method.